2021
DOI: 10.48550/arxiv.2107.01686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Many-body coherence and entanglement from randomized correlation measurements

Eric Brunner,
Andreas Buchleitner,
Gabriel Dufour

Abstract: We show that k-point correlation measurements on output of a non-interacting, multimode, random unitary allow to quantify the k-particle coherence of N ≥ k identical (bosonic or fermionic) particles. For separable many-particle input states, we establish an on average strictly monotonic relationship between such k-particle coherences, the interference contrast in the experimentally accessible counting statistics and the degree of the particles' mutual distinguishability, as controlled by their internal degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Another interesting direction consists in realizing recent proposals to access non-trivial n-body correlations [23,24]. These theoretical works have shown that nondiagonal correlators can be accessed from combining twoparticle unitary transformations -e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting direction consists in realizing recent proposals to access non-trivial n-body correlations [23,24]. These theoretical works have shown that nondiagonal correlators can be accessed from combining twoparticle unitary transformations -e.g.…”
Section: Discussionmentioning
confidence: 99%
“…works have shown that applying random unitary transformations before measuring the FCS provides access to non-diagonal correlators [23,24], further motivating the development of experimental approaches to the FCS, in particular in interacting systems. To reveal the many-body coherence properties of the trapped gas of size L, δk is chosen inferior to 1/L, δk × L 1.…”
Section: Introductionmentioning
confidence: 99%